Discovering JavaScript Object Notation. - Severance, Charles (Computer (00189162), 2012)
JSON is moving from being an underground secret, known and used by very few, to becoming the clear choice for mainstream data applications. The first Web extra is a video interview with Douglas Crockford on the creation of JavaScript Object Notation (JSON). The second Web extra is an audio podcast by Charles Severance, author of Computing Conversations.